Conditioned by the environment (Journal of Parents and Teachers, 2025)
Martin Rosenbaum, in his book Children and the Environment, recommends that parents ‘do not focus solely on the dangers of their child being hit by a car’ because the environment can be, insidiously, more harmful than all of that. This is not, of course, to alarm anyone, but rather to raise awareness of a series of precautions that everyone should take, especially young children, who are more susceptible to serious consequences. He outlines five new dangers (related to the environment) in the growth and development of children.
Keywords: environment, children, dangers, development, balance